Electrocardiographic reference parameters in healthy pug dogs - Choudhary, Sarthak; Saini, Neetu; Turkar, Sujata; Chhabra, Sushma (Indian Journal of Veterinary Medicine, 2024)
The present study was designed to establish electrocardiographic data in healthy Pug dogs with respect to body weight, age and gender. Forty clinically healthy pug dogs presented to Teaching Veterinary Clinical Complex, Guru Angad Dev Veterinary and Animal Sciences University presented for routine deworming, vaccination and general health check-up were selected for the present study. Fifteen dogs were in the body weight range of 1-7 kg and 25 dogs in 7-15 kg range. To study the effect of age on various electrocardiographic measurements dogs were divided into 3 age groups (1-3, 3-6 and >6 years of age). Heart rate was found to be high (146.3±7.7 bpm) ranging from 100-200 bpm in 1-7 kg body weight as compared 7-15 kg body weight 128.3±4.0 bpm ranging from 90-170 bpm although, there was no significant effect on mean heart rate. All the amplitudes and durations of electrocardiographic waves and complexes did not show any significant variation with respect to body weight. The heart rate belonging to age group 1-3 years was 148.08±8.76 bpm ranging from 100-200 bpm significantly high (p 6 years old (122.3±2.41 bpm) ranging from 105-135 bpm and there was no significant variation (p >0.05) in amplitude and durations of electrocardiographic data with respect to age. Heart rate was higher in females (140.74±6.25 bpm) ranging between 100 and 200 bpm than in males (129.90±4.99 bpm) ranging between 90 and 180 bpm but was found to be non-significant (p > 0.05). P-R interval, was found to be significantly (p < 0.05) higher in females as compared to males.